SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN BANTUAN SOSIAL MENGGUNAKAN ALGORITMATOPSIS(STUDI KASUS KAMPUNG CISIRAM) - Ainin Najmi; Fenny Fadilah; Ardhi Anggoro Mukti (Journal of Innovation And Future Technology, 2025)
To support and improve community welfare, the government has launched various social assistance programs such as JAMSOSRATU, the Family Hope Program (PKH), Direct Cash Assistance (BLT), Cash Social Assistance (BST), and Non-Cash Food Assistance (BPNT). The distribution of these programs is expected to be well-targeted, organized, and transparent. However, in practice, issues such as subjective assessments, invalid data, and lack of accuracy in beneficiary selection are still frequently encountered. To address these issues, this study proposes the development of a Decision Support System (DSS) using the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method. This method supports decision-making processes that are fast, objective, and efficient. The criteria used in the assessment include occupation, income, number of household members, and housing status. This research includes the stages of system analysis, design, implementation, testing, and maintenance. The results of system implementation show that the TOPSIS method provides more accurate and accountable outcomes in selecting social assistance recipients. This system is expected to assist the committee in determining BLT beneficiaries in Kampung Cisiram in a fair and appropriate manner.